2012
DOI: 10.1080/10810730.2012.713441
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Barriers to Colorectal Cancer Screening in Community Clinics

Abstract: This article examines the relationship between literacy and colorectal cancer (CRC) screening knowledge, beliefs, and experiences, with a focus on fecal occult blood tests (FOBTs). Participants were 975 patients in 8 Louisiana federally qualified health centers. Participants were 50 years of age or older and not up to date with CRC screening; approximately half (52%) had low literacy (less than a 9th-grade level). Participants with low literacy were less likely than were those with adequate literacy to be awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 14 publications
7
48
1
Order By: Relevance
“…In a similar vein, Greiner et al (2004) have found that older people and individuals with higher levels of education tend to participate more to the CRC screening programs. In another study, it has been found that individuals with lower levels of education have lower rates of awareness on CRC screening programs and that they are less likely to grasp the importance of early diagnosis of the colorectal cancer (Arnold et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, Greiner et al (2004) have found that older people and individuals with higher levels of education tend to participate more to the CRC screening programs. In another study, it has been found that individuals with lower levels of education have lower rates of awareness on CRC screening programs and that they are less likely to grasp the importance of early diagnosis of the colorectal cancer (Arnold et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Low health literacy is postulated to result in lower screening attendance through causing limited knowledge of health services and diseases, difficulty in understanding abstract concepts such as risk, a preference for emotional over factual information, and lower decision-making skills(von Wagner, Steptoe, et al, 2009). In the context of CRC screening, previous studies have shown that individuals with low levels of health literacy report more problems in seeking and processing health-related information (von Wagner, Semmler, Good, & Wardle, 2009), as well as barriers in understanding (Arnold et al, 2012;Peterson, Dwyer, Mulvaney, Dietrich, & Rothman, 2007) or completing screening (Kobayashi et al, 2014). In line with these hypotheses, we found that inadequate health literacy was associated with lower probability of screening uptake in univariate and multivariate models, and it contributed to nearly 8% of inequality.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed whether supportive family behaviors were associated with better glycemic control only among patients with limited HL (HL X supportive), or whether supportive behaviors were more likely to protect against the effects of obstructive behaviors on worse glycemic control among patients with limited HL (HL X supportive X obstructive). Because limited HL is common among patients who receive care at Federally Qualified Health Centers (FQHCs) (Arnold et al, 2012), we explored these hypotheses with a racially diverse sample of adults with T2DM receiving care at a FQHC.…”
mentioning
confidence: 99%